2017
DOI: 10.1165/rcmb.2016-0201oc
|View full text |Cite
|
Sign up to set email alerts
|

Roles for the CX3CL1/CX3CR1 and CCL2/CCR2 Chemokine Systems in Hypoxic Pulmonary Hypertension

Abstract: Monocytes/macrophages are major effectors of lung inflammation associated with various forms of pulmonary hypertension (PH). Interactions between the CCL2/CCR2 and CX3CL1/CX3CR1 chemokine systems that guide phagocyte infiltration are incompletely understood. Our objective was to explore the individual and combined actions of CCL2/CCR2 and CX3CL1/CX3CR1 in hypoxia-induced PH in mice; particularly their roles in monocyte trafficking, macrophage polarization, and pulmonary vascular remodeling. The development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 24 publications
3
96
1
Order By: Relevance
“…On the contrary, the exposure of macrophages to dexamethasone or cytokines, such as interleukin IL-4 and IL-13, leads these cells to adopt an anti-inflammatory profile that is characterized by the production of IL-10 and/or CD206 [15]. Furthermore, the exposure of macrophages to proor anti-inflammatory stimuli also affects the expression of molecules that are involved in leukocyte trafficking, such as CX3C-motif chemokine receptor 1 (CX3CR1) and C-C chemokine receptor type 2 (CCR2) [17,18]. More importantly, the inflammatory activation enhances the ability of macrophages to ingest bacteria with respect to that described in macrophages with anti-inflammatory functions [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the exposure of macrophages to dexamethasone or cytokines, such as interleukin IL-4 and IL-13, leads these cells to adopt an anti-inflammatory profile that is characterized by the production of IL-10 and/or CD206 [15]. Furthermore, the exposure of macrophages to proor anti-inflammatory stimuli also affects the expression of molecules that are involved in leukocyte trafficking, such as CX3C-motif chemokine receptor 1 (CX3CR1) and C-C chemokine receptor type 2 (CCR2) [17,18]. More importantly, the inflammatory activation enhances the ability of macrophages to ingest bacteria with respect to that described in macrophages with anti-inflammatory functions [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, other cell-surface chemokine receptors commonly expressed by Mo-MDSC, such as CCR2 and CX3CR1, are highly expressed in circulating immune cells accumulating within the lungs of mice with chronic hypoxia-induced pulmonary hypertension [79]. A direct role, however, for secreted CCR2 and CX3CR1 ligands in regulating the hemodynamic changes, beyond recruitment of inflammatory monocytes and indirect influence on pulmonary artery smooth muscle cell hyperproliferation, remains unproven [80].…”
Section: Myeloid-derived Suppressor Cells and Pulmonary Hypertensionmentioning
confidence: 99%
“…The importance of monocyte infiltration into the lungs in PH is relatively understudied. Recently, Amsellem et al showed that Cx 3 cr1 plays a major role in hypoxia-induced PH by modulating monocyte recruitment, macrophage polarization, and smooth muscle cell proliferation in the lungs[75]. Congruently, cx 3 cr1 -deficient mice had an attenuated PH pathogenesis.…”
Section: Importance Of Bone Marrow-derived Cells In Ph Pathogenesismentioning
confidence: 99%
“…For example, in the context of atherosclerosis, high levels of G-CSF suppress CXCL12 production by osteoblasts, leading to HSC proliferation and release [94, 95]. As discussed above, multiple studies reported blood and lung monocytosis in the context of PH [62, 75, 76]. The blood monocyte expansion depends on their generation in the bone marrow from hematopoietic stem and progenitor cells.…”
Section: Generation Of Inflammatory Myeloid Cells In the Bone Marrowmentioning
confidence: 99%
See 1 more Smart Citation